The Public Role of Perm Province in Assisting the Sick and Wounded Soldiers During the First World War - Kaydysheva Natalya (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2014)
On the example of Perm province the public activity on helping the sick and wounded soldiers during the World War I is analyzed. On the basis of wide scope of sources, the author investigates the participants, the scales and the forms of social help. The accent is made on the sources of financing organizations which carried out this activity. It is shown that all population layers in Perm province took part in rendering help to sick and wounded soldiers. The society often took the initiative in providing the charity events created by authorized structures that revealed the civil activity. The civil charity initiative gets further development during the war in mining plants. The state was interested and contributed to the civil independent actions, and it was caused by the wartime conditions. The author also determines the peculiarities of the assistance to sick and wounded soldiers in Perm province. All-Russian State Union became the body through which this help got better organized official registration during the war. It attracted major human resources and accumulated considerable monetary and clothing donations to the benefit of sick and wounded soldiers, thus providing the state with the possibility to control and coordinate this activity in the province.